Pemanfataan Media Powtoon Dalam Pembelajaran Fisika Untuk Meningkatkan Hasil Belajar Dan Keaktifan Siswa - Asmaul Khusna (Student Research Journal, 2024)
This research aims to improve the learning outcomes and activity of class XA MAN 4 Madiun students in Physics and Energy lessons through the use of Powtoon media. This research is classroom action research consisting of 2 cycles. The subjects of this research were all students in class XA MAN 4 Madiun, totaling 31 students. The data analyzed in this research are observation sheets, questionnaires and written test results. The data analysis technique was carried out using quantitative description techniques. The indicator of success for this research is that 75% of students have completed the KKM. In the pre-cycle, 48% (15) students completed the KKM. In the first cycle, 71% (22) students completed the KKM. Then, in cycle II there were 90% (28) students who completed the KKM. Research success was obtained in cycle II. The use of Powtoon learning media has also succeeded in increasing students' active learning as proven by the success indicator of this research being more than 75% of the number of students in the A and B grade classifications. The success of the research to increase students' active learning in class was obtained in cycle II, namely 83.9%. (26) students.